Exploring the Impact of Short Videos on Society and Culture: An Analysis of Social Dynamics and Cultural Expression - Chen, Lin (Pacific International Journal, 2023)
This study investigates the impact of short videos on society and culture. Short videos, which are brief video clips typically ranging from a few seconds to a few minutes in length, have gained immense popularity through various social media platforms. They have revolutionized the way people consume and produce media content, reshaped communication patterns and interpersonal relationships, and influenced social norms and values. Additionally, short videos have played a significant role in cultural expression, transforming cultural practices and traditions, influencing cultural diversity and identity, and shaping cultural consumption patterns. This research employs qualitative research methods, including interviews with participants from Nanjing Normal University Taizhou College, to explore the multifaceted impact of short videos on social dynamics and cultural expression. The findings provide insights into the implications and consequences of short videos, with recommendations for policymakers, content creators, and users.